Information sharing across mental health service providers and criminal legal system stakeholders: Perspectives of people with serious mental illnesses and their family members. (August 2022) - Pope, Leah G.; Warnock, Amanda; Perry, Tyler H.; Langlois, Stephanie; Anderson, Simone; Boswell, Tehya; Appelbaum, Paul; Dixon, Lisa; Watson, Amy; Compton, Michael T.
Abstract: Objective: The overrepresentation of people with serious mental illnesses in the criminal legal system has spurred information-sharing initiatives to transmit information between mental health service providers and criminal legal system stakeholders with the goal of improving resources and streamlining access to care. However, no research to date has examined the perspectives of people with mental illnesses who have their information shared across these systems or the perspectives of their family members. This study examined the perspectives on mental health-criminal legal system information sharing among people with serious mental illnesses and a history of arrest, as well as their family members. Methods: Researchers interviewed 24 clients with serious mental illnesses and a history of arrest who are enrolled in a randomized, controlled trial of a police-mental health Linkage System as well as 11 of their family members. Participants were recruited and interviewed between November 2020 and February 2021. A thematic analysis was used to code and analyze all interview transcripts. Results: Study participants articulated perceived benefits and concerns around cross-system information sharing. There was strong support for information sharing in both directions, with the anticipation that such information sharing can prevent unnecessary arrest and/or incarceration, promote positive and safe interactions with criminal legal system professionals, and foster greater understanding and access to treatment. Concerns were more limited and largely related to perceived stigma around mental illnesses and the potential consequences of such stigma. Conclusions: While concerns about information sharing should be considered, study participants overwhelmingly perceived the sharing of information between mental health providers and criminal legal stakeholders as a positive intervention. Such perspectives can be understood as a pragmatic choice in the face of criminal legal system contact and additional research could guide programmatic and policy changes. Highlights: Sharing mental health information with criminal legal system providers is increasingly common. Interviews were conducted with people with SMI and arrest histories and their family members. Participants believed benefits to cross-system information sharing outweighed risks. Concerns are related to the collateral consequences of stigma around mental illness.